Evaluation of the Efficacy and Safety of Chinese Herbal Injection Combined With Trimetazidine for Viral Myocarditis: A Network Meta-Analysis - Wu, Kerui; Deng, Dingwei; Yu, Binghui; Han, Ziyun; Huang, Lanlin; He, Yaxing; Yan, Xia; Wang, Dawei (Frontiers in Pharmacology, 2021)
Background:Viral myocarditis is a common emergency of cardiovascular disease. Due to the lack of specific drugs, the treatment is mainly based on support and symptomatic treatment.Trimetazidine,a drug in improving myocardial energy metabolism,is often used in the treatment of it.In China,Chinese herbal injections are often used in combination.Therefore, we evaluate the efficacy and safety of Chinese herbal injections combined with trimetazidine in the treatment of viral myocarditis through the method of network meta- analysis. Methods: Retrieving relevant databases to obtain clinical randomized controlled trials of Chinese herbal injection combined with trimetazidine in the treatment of viral myocarditis. According to inclusion and exclusion criteria, the literature was screened and the included studies were determined. The cochrane risk assessment tool was used to evaluate the methodological quality of the literature, and the Stata 16.0 software was used to perform the network meta-analysis. Results: A total of 29 studies were included, including 2687 patients. The effectiveness rate,the level of marker of myocardial injury(creatine kinase,creatine kinase-MB,lactate dehydrogenase and cardiac troponin I) and the adverse reactions were evaluated.The results show that compared with conventional therapy or conventional therapy combined with trimetazidine,Chinese herbal injection combined with trimetazidine may have a better therapeutic effect, with higher effectiveness rate and better reduction effect in the level of creatine kinase,creatine kinase-MB and lactate dehydrogenase.Based on SUCRA ranking, in terms of effective rate, shenmai injection combined with trimetazidine may be the better choice,and astragalus injection or salvia miltiorrhiza and ligustrazine hydrochloride injection combined with trimetazidine may be the better choice in terms of reducing myocardial enzyme.In terms of adverse reactions, there is no significant difference in their comparison.As part of the included studies did not have safety reports, the safety of some Chinese herbal injections could not be assessed. Due to the limitations of the included studies, the results of this study still need further clinical verification. Conclusion:Chinese herbal injections combined with trimetazidine may have a better therapeutic effect in the treatment of viral myocarditis,and shenmai injection, astragalus injection and salvia and ligustrazine hydrochloride injection may be the better choice.Nevertheless, this study still needs more high-quality clinical trials to verify it.